Psychometric evaluation of the Chinese version of fear of hospitalization scale among outpatients: A validation study - Li, Wenbo; Yu, Hongyu; Zhang, Yanli; Li, Bing; Fu, Mingshu (Frontiers in Psychology, 2023)
Background In China, some patients avoid seeking medical care and are highly sensitive to subsequent medical care because of fear of possible hospitalization after a diagnosis has been established. Early identification of fear of hospitalization is essential for clinical staff to develop targeted education and interventions. However, there are currently no tools to assess outpatients’ fear of hospitalization in mainland China. This study aimed to translate the Fear of Hospitalization (FH) scale into Chinese and verify its reliability and validity in outpatients. Methods Through convenience sampling, 664 outpatients who required hospitalization were recruited from two cities in Liaoning Province, China. The reliability of the translated scale was measured by internal consistency, split-half reliability, and test–retest reliability. The validity of the translated scale was evaluated by expert consultation, exploratory factor analysis, and confirmatory factor analysis. Data were analyzed using SPSS 25.0 (IBM Corp., Armonk, NY, United States) and AMOS 23.0 (IBM Corp., Armonk, NY, United States). Results The Cronbach’s α value of the Chinese version of the FH scale was 0.849, and the Cronbach’s α value of the dimensions ranged from 0.857 to 0.902. The test–retest reliability value of 0.868 shows good temporal stability. The split-half reliability value of 0.910 indicates a high degree of measuring the same content. The content validity index of the scale (S-CVI) was 0.924, indicating a good level of content validity. The 3-factor structure supported by eigenvalues, total variance explained, and scree plot was obtained using exploratory factor analysis. In addition, all recommended fit indicators were within the acceptable range by confirmatory factor analysis. Conclusion The Chinese version of the FH scale is valid and reliable in outpatients. The developed three-factor structured scale will help identify outpatients with a high fear of hospitalization and can inform the development of educational intervention plans for care managers, physicians, and nurses. In addition, it helps clinicians and nurses take action to reduce this fear of hospitalization in patients and prevent avoidance of using health care services due to fear of hospitalization.